Clinical and Epidemiological Characteristics of Severe and Very Severe Pneumonia in Infants - Mustiko MD, Hedi; Setyoningrum MD, Retno Asih (PT Dexa Medica, 2020)
Background: Childhood pneumonia is a leading cause of mortality and morbidity in developing countries. World Health Organization (WHO) stated that pneumonia is the cause of mortality of around 1.2 million children under 5 years per year. The high incidence of very severe pneumonia cases with preventable risk factors become the background of this study.Purpose: The aim of our study was to describe clinical and epidemiological characteristics of severe and very severe pneumonia in infants and children.Methods: This is a descriptive cross-sectional study. The study were conducted from January 2017 to December 2018. We obtained clinical and demographic data of each patient based on medical records.The diagnosis of pneumonia was made clinically based on the Indonesian Ministry of Health criteria. Prematurity was defined as babies born with gestational age less than 37 weeks, low birth weight was defined as babies with birth weight less than 2500 grams. The nutritional status of children is clinically and anthropometrically evaluated using 2006 WHO curve of weight-by-age. Results: A total of 465 patients were diagnosed with pneumonia during 48 months study. 212 patients were excluded and 253 pneumonia patients met the inclusion criteria, 140 patients with very severe pneumonia and 113 patients with severe pneumonia. Among 253 patients, 141 were boys. 125 patients were 2-5 months of age. 71 patients were born with low birth weight and 62 patients had history of preterm birth. There were 86 patients receiving exclusive breastfeeding and 138 patients with complete immunization status. There were 131 patients with moderate and severe malnutrition, and 127 patients with comorbidity factors. 94 patients developed pneumonia with suspected bacterial causative agents.Conclusion: Lower age, prematurity, low birth weight, poor nutritional status, exclusive breastfeeding, comorbidities, and suspected bacterial causative agents are common characteristics of severe and very severe pneumonia in infants and children in Dr. Soetomo Surabaya.